Implementation of DSN-MUI Fatwa No. 108 Year 2016 on Hospitality in Aceh; Grand Permata Hati, Ayani Hotel, and Oasis Atjeh Hotel - Mulyadi, Deni (Jurnal Ilmiah Ekonomi Islam, 2024)
This study describes the implementation of the DSN-MUI fatwa No. 108 of 2016 concerning guidelines for hotel management based on Sharia principles at the Grand Permata Hati Hotel, Ayani Hotel, and Oasis Atjeh Hotel. The purposes of this study are to find out the implementation of the DSN-MUI Fatwa No. 108 of 2016 and to find out the obstacles in its implementation at the three hotels. This field research uses qualitative descriptive analysis techniques through a qualitative descriptive approach. The results of this study conclude that: first, Grand Permata Hati Hotel, Ayani Hotel, and Oasis Atjeh Hotel have implemented 6 out of 7 sharia hotel provisions in DSN-MUI No. 108 of 2016. Second, the obstacles that caused the DSN-MUI fatwa not to be fully fulfilled are because, 1) apart from using sharia financial services by Grand Permata Hati, Ayani Hotel, and Oasis Atjeh Hotel, the hotels are still unable to leave conventional financial services. 2) There are still many hotel guests using conventional services in making transactions, generally they come from outside the province of Aceh and still depend on these banking services.